Exploring correlation between social determinants and overweight/obesity in children and youths with epilepsy - Yang, Jie; Chen, Fang (Frontiers in Pediatrics, 2022)
Aim: The study was to explore the correlation between social determinants and overweight and obesity in children and youths with epilepsy. Methods: The study data were derived from the National Survey of Children’s Health (NSCH) 2016-17 and 2018-19, a cross-sectional sample of young people aged 10-17. Three groups participated by weight: 423 in body mass index (BMI) 5th-84th group (normal weight), 108 in BMI 85th-94th group (overweight) and 124 in BMI≥95th group (obesity). Multivariate ordinal logistic regression analyses were conducted. Then three subgroups were divided to explore the correlation between social determinants and overweight and obesity. Results: A total of 655 children were included. After adjusting sex, age, race, use of cigarettes, cigars, or pipe tobacco inside, afterschool activity, and physical activity, children in poor physical condition reported by their parents [OR=1.573 (95%CI: 1.164–2.125)] and sedentary screen time [OR=1.592 (95%CI: 1.078–2.352)] were associated with overweight/obesity. There were negative correlations between parents with higher education and overweight/obesity, especially in children and youths with previous or current epilepsy groups. Also, overweight/obesity was correlated with the 200-400% family poverty level (FPL) [the adjusted OR=0.156 (95%CI: 0.028-0.876)] and above 400% FPL [the adjusted OR=0.121 (95%CI: 0.023-0.641)] in children and youths with mild symptoms of epilepsy, and above 400% FPL [the adjusted OR=0.103 (95%CI: 0.023-0.460)] in children with moderate to severe epilepsy. Conclusion: Poor physical conditions were correlated with obesity in childhood epilepsy. Parents with higher education and family poverty levels were negatively correlated to childhood obesity. Therefore, this study was intended to advocate more focus on BMI for children and youths with epilepsy in families with lower-educated and low-income groups.